Prospects and Scope of Olive Mechanization: A Review (Zoo Botanica, 2023)
Olive is one of the most globally recognized high-value crop mostly utilized for its oil, with 4 million hectares cultivated in the Mediterranean area. The production procedure involves many stages: nursery raising, out-planting, interculture, irrigation, plant protection, pruning, harvesting and processing. Each stage is very important and for this purpose, the entire sector is implementing strategies for mechanization of the whole production process for more economical, time-saving, and sustainable processes. This review aimed to carry out an overview of mechanization in olive production and its processing. Related literature has been thoroughly studied, highlighting the increase in the adoption of mechanical approaches in the olive production process. The results of the review reflect diversification in the field of mechanization throughout the olive production process. The use of mechanization in nursery raising, out-planting, interculture, irrigation, plant protection, pruning, harvesting, and processing has a great impact on the whole production cycle. Special focus was given to major machinery used from olive planting to processing.
Keywords: Harvesting; Interculture; olive; processing; production; pruning